An ACE2 PET imaging agent derived from 18F/Cl exchange of MLN-4760 under phase transfer catalysis - Pan Zhou; Kai Ning; Shuai Xue; Qingqing Li; Danni Li; Haijun Yang; Zeying Liang; Rou Li; Jian Yang; Xiao Li; Lan Zhang (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Angiotensin-converting enzyme-2 (ACE2) acts as a key regulatory molecule and important therapeutic target in the pathological remodeling of numerous organs and diseases. In this study, a rapid, simple, and efficient synthetic route with a catalytic, 18F-for-Cl (18F/Cl) exchange scheme was designed for the preparation of 18F-labeled MLN-4760, and its targeting ability was investigated in a humanized ACE2 mouse model. Results A novel 18F-labeled MLN-4760 radioligand, abbreviated as 18F-MLN-4760, was successfully synthesized by the 18F/Cl exchange-labeling, and was purified by SepPak C18 columns with a radiochemical yield of 30% and a radiochemical purity of 29.89%. Target distribution of 18F-MLN-4760 in several organs with high ACE2 expression was observed by PET imaging with good stability over 120 min. The biodistribution data showed that the uptake of 18F-MLN-4760 in ACE2-overexpressing organs and tissues was highly specific, and immunohistochemistry confirmed the same results of ACE2 expression and biodistribution in the major organs (heart, liver, lungs, and kidneys). There was a good correlation between the uptake in the organs with high ACE2 expression and ACE2 expression levels (r = 0.935). Conclusion 18F-MLN-4760 was successfully synthesized via 18F/Cl exchange under phase transfer catalysis, and served as a potential probe for ACE2-targeted PET imaging.